Hubungan Kecerdasan Emosional dengan Tingkat Forgiveness pada Remaja di SLTA Kecamatan Montong - Hanim Nur Faizah; Dela Ayu Firnanda; Karyo Karyo; Lukman Hakim (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Forgiveness can be described as a response given by someone who has experienced hurt in order to avoid revenge and expressions of anger towards the perpetrator, while choosing to show compassion, affection, love, and positive behavior. One of the factors that influence forgiveness is emotional intelligence, which includes an individual's ability to motivate themselves, show resilience to failure, control emotions, maintain satisfaction, and regulate psychological conditions. The purpose of this study was to determine whether there is a relationship between emotional intelligence and the level of forgiveness among high school students in Montong District. This research is non experimental with a correlational analytical design using a cross sectional approach. The research population included 592 high school students in Montong District. The sampling technique applied was probability sampling with cluster random sampling, resulting in a sample of 239 students. Data collection was conducted using questionnaires that measured emotional intelligence and forgiveness. The results of the analysis using the Spearman test at α = 0.05 showed p = 0.000 < 0.05 with a correlation coefficient of r = 0.389, indicating a low relationship between the two variables, thus accepting the hypothesis. Based on this description, it can be concluded that there is a relationship between emotional intelligence and the level of forgiveness among high school students in Montong District.